Avaliação da toxidade aguda do fungicida Tebuconazole utilizando o organismo teste Daphnia magna - Cupertini, Patricia Mara (2017)
The agrochemicals have acquired over time new characteristics that guarantee them greater solubility in water, decrease in the adhesion capacity and increase in the volatilization. These factors lead to the easy transport by rainwater and they can act as a source of surface water contamination. Toxicology together with the acute toxicity tests are intended to help assess the effects of these substances on exposed organisms. Thus, the present study aimed to verify the acute toxicity of the fungicide Tebuconazole to three generations of the microcrustacean Daphnia magna. First generation neonates were obtained from the culture lots without exposure to the substance. The tests performed with the second generation were simulated in two different conditions, (1) the parental organisms being individually exposed in chronic condition and (2) exposed in lots under subacute conditions. The third generation neonates were obtained from the parental organisms of the 2nd generation exposed in chronic condition. Acute tests performed for the 1st generation indicated high toxicity, with EC50,48h of 631,4 μg/L. The results of the acute toxicity tests for the 2nd generation demonstrated greater sensitivity of the organisms for both situations that were tested. However with a longer period of follow-up it was possible to verify that they are now resistant to Tebuconazole. This effect was verified by comparing EC50,48h obtained in this period, with the results of acute toxicity verified with the first organisms of the 2nd generation. The results verified for the 3rd generation demonstrate this resistance acquired by the organisms, and the neonates from organisms exposed in the concentration of 60 μg/L, presented EC50,48h higher than the one found for organisms of the 1st generation. Even if the organisms show signs of acquiring substance resistance over time, it is necessary to observe the acute toxicity verified for them, since the substance has proved to be extremely toxic and, therefore, it can be a potential cause of environmental contamination, which compromises the life of the organisms in the aquatic environment and consequently it can have effects on the balance of the system.